(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ethnobotany was worked to incorporate plant concentrates as well as investigations of green growth, lichens, and parasites. It is firmly connected with the science of scientific classification, pharmacognosy, phytochemistry, environment, and preservation. So as to feature the therapeutic utilization of plants and there pharmacological angles, this article audits various ethnobotany messages and papers, and furthermore clarifies the extent of ethnobotany. It incorporates a concise survey of ethnobotany in India, onpast, present and future.